Effect of different temperature on structural, magnetic and dielectric properties of strontium hexaferrite powder synthesised using aloe vera plant extracts - Solanki, Neha; Jotania, R. B.; Khomane, Ramdas B.; Kulkarni, B. D. (Advanced Science Letters, 2016)
M-type SrFe12O19 hexaferrite particles synthesized using the aloe vera plant extract. Biological materials of microorganisms, plants, enzymes have been suggested as an ecological alternative for conventional reagents in physical and chemical methods. In present paper we report effect of temperature on structural, morphology, magnetic and dielectric properties of M-type SrFe12O19 particles synthesised by Green synthesis technique using Aloe vera plant extract. The metal nitrates (Sr and Fe) were dissolved in aloe vera extract solution and then mixture was kept in oil bath at 100 degrees C till it become dry. The obtain dried powder calcined in a wide temperature range, from 450 degrees C to 1150 degrees C for 4 hours in a static air atmosphere. The calcined powders were characterised using various instrumental techniques like Fourier transform infrared spectroscopy (FTIR) X-ray diffractometry (XRD), Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Vibrating Sample Magnetometry (VSM), and dielectric measurements. XRD, FTIR, SEM, Magnetic and dielectric measurements were carried out at room temperature. XRD analysis confirms the formation of mono phase of strontium hexaferrite at 1150 degrees C.
Keywords: Aloe Vera Extract; green synthesis; M-Type Hexaferrite; Strontium Hexaferrite